Multilocus Sequence Analysis highlights genetic diversity of Acidovorax avenae strains associated with sugarcane red stripe - Fontana, Paola Daniela; Tomasini, Nicolás; Fontana, Cecilia Alejandra; Di Pauli, Valentina; Cocconcelli, Pier Sandro; Vignolo, Graciela Margarita; Salazar, Sergio Miguel (International Society of Sugar Cane Technologists, 2021)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019